Error Analysis in the Use of English Articles among Uzbek EFL Learners - Norpoʻlatova Nozima Yusufxon qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article investigates the common errors made by Uzbek learners of English as a Foreign Language (EFL) in the use of English articles “a”, “an”, and “the”. English articles present considerable difficulty for Uzbek learners due to typological differences between English and Uzbek, as Uzbek does not possess a direct article system. The study examines the main types of article-related errors, including omission, addition, substitution, and misuse in generic and specific contexts. It further analyzes the linguistic causes of these errors, such as first-language (L1) interference, overgeneralization of rules, limited exposure to authentic input, and insufficient metalinguistic awareness. Based on classroom observations, learner writing samples, and previous research findings, this paper provides pedagogical implications and practical recommendations to improve article usage among Uzbek EFL learners. The results suggest that explicit instruction, contextualized practice, and corrective feedback play a crucial role in reducing article-related errors and enhancing accuracy in English writing and speaking.